Volunteerism and democratic learning in an authoritarian state: the case of China. Issue 5 (4th July 2022) - Teets, Jessica C.; Hasmath, Reza; Hildebrandt, Timothy; Hsu, Carolyn L.; Hsu, Jennifer Y.J.
ABSTRACT: Extant literature on civic participation in Western democracies demonstrates a linear relationship between increased civic participation and a stronger democracy. In general, the scholarly debate revolves around the precise causal mechanisms for this relationship: holding government accountable; citizens learning "democratic skills", such as collective mobilization and advocacy; and, building social capital and trust to overcome the dilemma of collective action. Given rapidly increasing volunteerism in China, this study tests these theories in a single-party authoritarian system using evidence from the 2020 Civic Participation in China Survey. The study finds that volunteers in China do learn "citizen skills"; however, these differ from those learned by volunteers in democracies. Foremost, while volunteering allows for authoritarian citizens to learn and differentiate channels most appropriate for addressing specific social problems, they generally do not try to directly hold their government accountable for poor performance. Additionally, the study finds limited support that volunteers are seeking to develop trust in other citizens, contra evidence from Western democracies. Finally, the results suggest that volunteers are participating as a means to send signals to the state that they are emerging local community leaders. These findings have important implications for increasing civic participation in authoritarian regimes.